Optimizing bookstore production using fuzzy linear programming / Suzanawati Abu Hasan, Teoh Yeong Kin and Diana Sirmayunie Mohd Nasir - Abu Hasan, Suzanawati; Teoh, Yeong Kin; Mohd Nasir, Diana Sirmayunie (UiTM Cawangan Perlis, 2018)
The world Reader bookstore has a structured collection of books neatly arranged on shelves. The question is how the bookstore should keepthe shelves full and make profit at the same time. Books are expensive due to the building tax that the business owner needs to pay, along with the tax imposed on each book. Hence, a bookstore owner will typically increase the prices of the books to make profit. Due to the high prices, people are keener to buy books through online store. Thus, this study is conducted to optimize books needed to be sold in a bookstore using the fuzzy linear programming approach. This study will focus more on fiction and non-fiction books that are available in the bookstore, which will help the bookstore to achieve its highest profit in the future. The result shows that the profit in a closed interval of [RM209016.00, RM348691.20] was obtained once the fiction and non-fictionbooks were [0 unit, 8000 units] and [4000 units, 4000 units]. Based on the findings of the study, other businesses can also use this method in to optimize their business in the future.